Structural and functional partitioning of bread wheat chromosome 3B - Choulet, Frédéric; Alberti, Adriana; Theil, Sébastien; Glover, Natasha; Barbe, Valérie; Daron, Josquin; Pingault, Lise; Sourdille, Pierre; Couloux, Arnaud; Paux, Etienne; Leroy, Philippe; Mangenot, Sophie; et al. (Science (New York, N.Y.), 2014)
We produced a reference sequence of the 1-gigabase chromosome 3B of hexaploid bread wheat. By sequencing 8452 bacterial artificial chromosomes in pools, we assembled a sequence of 774 megabases carrying 5326 protein-coding genes, 1938 pseudogenes, and 85% of transposable elements. The distribution of structural and functional features along the chromosome revealed partitioning correlated with meiotic recombination. Comparative analyses indicated high wheat-specific inter- and intrachromosomal gene duplication activities that are potential sources of variability for adaption. In addition to providing a better understanding of the organization, function, and evolution of a large and polyploid genome, the availability of a high-quality sequence anchored to genetic maps will accelerate the identification of genes underlying important agronomic traits.
Keywords: Triticum; chléb; pšenice; transpozibilní elementy DNA; Meiosis; rostlinné proteiny; chromozomy rostlin; Chromosomes, Plant; Bread; meióza; segregace chromozomů; DNA Transposable Elements; Recombination, Genetic; pseudogeny; rekombinace genetická; Pseudogenes; Polyploidy; Chromosome Segregation; Plant Proteins; polyploidie